Seed viability assessment of Campolay fruits (Lucuma campechiana) across varying weights and storage periods - AULIA HASAN WIDJAYA; DIAN LATIFAH; ENGGAL PRIMANANDA; RIZMOON NURUL ZULKARNAEN; ARIFAH RAHAYU (Nusantara Bioscience, 2024)
Abstract. Widjaya AH, Latifah D, Primananda E, Zulkarnaen RN, Rahayu A. 2024. Seed viability assessment of Campolay fruits (Lucuma campechiana) across varying weights and storage periods. Nusantara Bioscience 16: 23-28. Campolay (Lucuma campechiana Kunth), a locally cultivated fruit in West Java, Indonesia, has become popular in gardens and yards, although its trading activity remains relatively limited. The methods used for propagating this fruit include seeds, grafting, and layering. However, hard and impermeable seed coats present a challenge in germination. This research aims to investigate the impact of seed weight and storage duration on the viability of Campolay seeds. This will be done by employing a factorial, completely randomized design. The study will examine various variables related to germination, including total germination, germination rate, simultaneity, time to achieve 50% germination, time to first germination, and time to final germination. Although these factors do not significantly affect total germination, it was observed that seeds stored for longer periods, up to 6 weeks, exhibited higher germination rates and faster germination times. Interestingly, the seeds' weight did not impact germination, and there was no interaction between the duration of storage and the seed weight. The overall capacity for seed germination ranged from 92% to 97%. These findings indicate that storing Campolay seeds in moist sawdust under dark conditions can delay germination, which ensures a more consistent and uniform sprouting process. Moreover, this approach can also aid in the transportation of the seeds and support programs aimed at conserving plant germplasm.